Extremism: Nature, Symptoms, Experience and Conditions of Counteraction - Alexander Ivanovich Kugay (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to extremism, the study of its nature, symptoms and experience of counteraction. For the extremist does not exist diverse world. This is the subject with the most narrow minded, obsessed with one identity. He is ruthless and malevolent attitude towards everything and everyone except one. He believes that is the one that saves, but all the other kills. It is therefore necessary to devote oneself completely to this one and mercilessly destroy everything else, the whole multiple world that threaten. Extremist always in the way: a) in the mask, in which he clothed himself (“native fanatic”) - “leader”, “truth-bearer”, “the conscience of the nation”, “media genuine faith”, etc. or in the mask, in which it is clothed (“induced fanatic”) - “superethnos”, “avenger”, “hegemonic/dominant class”, “revolutionary”, “soldier”, “soldier”, “Shahid”, “Russian”, etc.; b) in the mask, relieves pain and responsibility; it is easier to pick up someone else’s mask, than to find his true face. Extremism produce the desire for recognition, envy, reckless self-righteousness. The article discusses the technology of combating extremism in Saudi Arabia - the country with the lowest level of recidivist extremist activity. To overcome the enmity and distrust, we must not only accept a certain loss of identity, but also to learn to live in a kaleidoscope of identities.